International students' with scholarships' academic experiences at Linton University College, Malaysia - Adekalu, Samuel Olutokunbo; Ismail, Ismi Arif (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The rate at which most organizations and institutions of higher learning offered scholarship education to attract international students is becoming competitive among citizens of the developed and developing nations who seek to have international education experience for better career opportunities and development. The paper reports on the study conducted among a group of international students in Negeri Sembilan State, Malaysia. The objective of the study is to explore general academic experience of international students with scholarship. In-depth interviews were conducted among Petroleum Technology Development Fund (PTDF) scholarship students at Linton University College. The results revealed that majority of the participants are generally satisfied and are able to cope with the classroom teaching, host community, renewal of students’ visa pass, academic adjustment and knowledge gained at Linton University College. Malaysia. Initiatives to improve international student academic experience studying abroad are recommended.